Optimum media compositions for bioprotein production by mixed culture of Phanerochaete chrysosporium and Candida utilis using palm kernel cake and seaweed as substrates - Ilias, Nurul Najihah; Jamal, Parveen; Sulaiman, Sarina; Jaswir, Irwandi; Ansari, Abdul Haseeb; Azmi, Azlin Suhaida; Zainudin, Zaki (Faculty of Food Science & Technology, Universiti Putra Malaysia, 2017)
Bioprotein is one of the useful products obtained from biotechnology invention. It is a promising replacement for the commercial fish feed supplement. In this study, the enrichment of the bioprotein content after solid state fermentation using palm kernel cake and seaweed by the white rot fungus: Phanerochaete chrysoporium and yeast: Candida utilis was carried out. The growth media components were selected from 11 types of media using Plackett-Burman design (hereinafter PBD) and were optimized by one-factor-at-a-time (OFAT) method with bioprotein concentration (mg/g) as the response. From the screening result using PBD, three media components, namely K2 HPO4 , CuSO4 .5H2 O and MnSO4 .H2 O were selected for further optimization using OFAT method because of their positive contributions to the response. The final results showed that 5.0 g/L K2 HPO4 , 3.0 g/L CuSO4 .5H2 O and 0.1 g/L MnSO4 .H2 O were there to be the optimum media constituents with 9.0 g/L, MgSO4 .7H2 O, 0.1 g/L, CaCl2 .H2 O, 3.0 g/L FeSO4 .7H2 O and 3.0 g/L peptone as fixed compositions. At this optimum concentration, the protein increment of 11% was observed as compared to the results determined in the screening using PBD. The study revealed the benefits of using mixed cultures in improving the protein concentrations which can be used as nutritious fish feed.